2019
DOI: 10.3847/1538-4357/ab10d9
|View full text |Cite
|
Sign up to set email alerts
|

Optical Counterparts of ULXs and Their Host Environments in NGC 4490/4485

Abstract: We report the identification of the possible optical counterparts of five out of seven Ultraluminous X-ray Sources (ULXs) in NGC 4490/4485 galaxy pair. Using archival Hubble Space Telescope (HST) imaging data, we identified a single optical candidate for two ULXs (X-4 and X-7) and multiple optical candidates for the other three ULXs (X-2, X-3 and X-6) within ∼ 0. 2 error radius at the 90% confidence level. Of the two remaining ULXs, X-1 has no HST imaging data and photometry could not be performed due to the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Most of the weaker in the optical range ultraluminous X-ray sources (with M V > −5. m 5) are objects with relatively "cold" energy distributions corresponding to supergiants of classes A-G (Avdan et al, 2016(Avdan et al, , 2019, which may indicate the predominance of the contribution of donor stars over the contribution of hot winds of supercritical disks . The reason for small contribution of wind radiation may be lower accretion rates in these objects.…”
Section: Optical Counterpartsmentioning
confidence: 99%
“…Most of the weaker in the optical range ultraluminous X-ray sources (with M V > −5. m 5) are objects with relatively "cold" energy distributions corresponding to supergiants of classes A-G (Avdan et al, 2016(Avdan et al, , 2019, which may indicate the predominance of the contribution of donor stars over the contribution of hot winds of supercritical disks . The reason for small contribution of wind radiation may be lower accretion rates in these objects.…”
Section: Optical Counterpartsmentioning
confidence: 99%
“…The studies in the optical band showed that majority of the ULXs are found to be associated with star forming regions or star clusters (Patruno & Zampieri 2010;Grisé et al 2011;Poutanen et al 2013;Avdan et al 2016Avdan et al , 2019Egorov et al 2017;Urquhart et al 2018). These associations were supported by the counterparts of ULXs as early type OB stars due to their observed blue color (Liu et al 2004;Grisé et al 2005;Soria et al 2005;Roberts et al 2008;Poutanen et al 2013).…”
Section: Introductionmentioning
confidence: 93%
“…Although there are hundreds of ULXs known, only about 20 have singled out optical counterparts (Tao et al 2011;Gladstone et al 2013;Avdan et al 2019). For many other ULXs, multiple undecidable optical counterparts have been detected (Soria et al 2005;Mucciarelli et al 2007;Avdan et al 2016bAvdan et al , 2019Aksaker et al 2019). Mostly, they have very faint optical candidates showing star-like spectral energy distributions (SEDs).…”
Section: Introductionmentioning
confidence: 99%